Necessary and sufficient conditions for deploying hydrogen homes: A consumer-oriented perspective - Gordon, Joel A.; Balta-Ozkan, Nazmiye; Haq, Anwar; Nabavi, Seyed Ali (International journal of hydrogen energy, 2024)
As part of its efforts to secure a ‘net-zero society’, the UK government will take a strategic decision on the role of hydrogen in decarbonising homes within the next years. While scholars have recently advanced the social science research agenda on hydrogen technology acceptance, studies are yet to engage with the prospective dynamics of adopting ‘hydrogen homes’. In response, this study examines the perceived adoption potential of hydrogen heating and cooking technologies, as evaluated through the eyes of consumer. Engaging with behavioural and market acceptance, this research draws on data from a broadly nationally representative online survey to examine the influence of safety, technological, economic, environmental, and emotional factors on the domestic hydrogen transition in the UK context. The analysis follows a multi-stage empirical approach, integrating findings from partial least squares structural equation and necessary condition analysis to crystallise insights on this emergent subject. At this juncture, perceived adoption potential may hinge primarily on emotional, environmental, safety, and to a lesser extent, technological perspectives. However, consumers have an expressed preference for hydrogen heating over hydrogen cooking, with perceived boiler performance emerging as a necessary condition for enabling adoption potential. At the formative phase of the transition, risks associated with energy insecurity and fuel poverty exceed concerns over purchasing and running costs. Nevertheless, economic factors remain less critical during the pre-deployment phase of the innovation-decision process. Across the full sample, simple slope analysis highlights the moderating effects of gender, age, and housing tenure. Moreover, statistically significant differences from both a sufficiency- and necessity-based perspective are detected between male property owners aged 55+ and female mortgage owners 18–34 years old. By bridging the knowledge gap between social acceptance and adoption intention, this contribution reinforces the need for consumer engagement in the hydrogen economy, advocating for more fine-grained, mixed-methods analyses of technology acceptance dynamics to support decarbonisation strategies. [Display omitted] •Economic factors constrain the perceived adoption potential of hydrogen homes.•The emotional dimension of hydrogen acceptance is highly influential.•Perceived adoption potential is contingent on safety and environmental perspectives.•Gender, age, and housing tenure status are potentially powerful moderators.•The role of hydrogen cooking warrants justification ahead of policy decisions.